Transsectoral investigation of a showing of the sense of the human energy (Studing rewiewing the book of prof. PhD Chaslav Koprivitsa: Philosophy of engagement) - Petrovic, Aleksandar M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The book of Chaslav Korprivitsa: Philosophy of engagement is treat in review by her presentation form, by the engaging to take up knowledge contents and statements. Dynamical mode of occupying of horizon of a sense of things, started with a problem of a contemporal dimension of significance the concept of world and human, contemplating the problem engagement in aspect of understanding of existence, education and consecratedness, dedicate to the heuristic way of the real truthness. Mutual understanding in a modeling of communicative acts, who collecting the parts, fractions from the crisis of modern world, and united themselves on the question of his possible wholeness, it is the way of the open significances to the overcoming of that crisis. The straightening on that way is taking by the intersubjective overcoming the difficultyes and idistinctness, as a encouraging releasing and more facultative liberation for the truth alone.